Integrating livelihoods and forest conservation through beekeeping in northern KwaZulu-Natal. Issue 4 (3rd July 2020) - Ricketts, K.; Shackleton, C. M.
ABSTRACT: South Africa has potential to export honey products through promoting beekeeping as an income generating opportunity amongst rural communities. Formalised beekeeping may also reduce wild fires initiated by hunters of wild bee hives. This study examined the contribution of the African Honey Bee (AHB) initiative to rural livelihoods and the incidence of forest fires using a mixed methods approach. The initiative increased incomes of newly trained and active beekeepers, although success rates and honey yields were variable. Core challenges included not catching bees, theft and vandalism of hives, insufficient bee forage, drought and pests. Most respondents also perceived an increase in crop size since AHB began, although few attributed this to pollination from the bees. The number of wild fires attributed to honey hunters more than halved after AHB began. Future steps need to reduce the challenges and integrate beekeeping into broader agriculture and forest conservation programmes.